If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -3x + 2 = -8 Reorder the terms: 2 + -7x + -3x = -8 Combine like terms: -7x + -3x = -10x 2 + -10x = -8 Solving 2 + -10x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -10x = -8 + -2 Combine like terms: 2 + -2 = 0 0 + -10x = -8 + -2 -10x = -8 + -2 Combine like terms: -8 + -2 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| 2x^2+4y^2-4x-24y+36=0 | | (2x-3)/7=(3x)/7-2x | | p^3-4p^2-p+4= | | 2.2q-3.9-2.8q=-1.6q-1.8 | | 4n=m(5-n) | | 3x^2-10x-28=0 | | -x^2+14x-57=0 | | -10=30 | | 64=2a+a^2+1 | | 2x^3+x^2-4x-3=0 | | x+4=2(.4x+1.3) | | 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) | | 5x-13=4(2x-5) | | 5b+6-6b+2= | | 9x^2-32=40 | | 5.5q-4.6-6.6q=2.2-1.1q-2.4 | | 6.1x+3=5.1x | | 10(-2x+1)=-12(x+2)+34-8x | | 7x+9-8x+4=6x-7x-5 | | 7x+3=3+7x | | 7x+4y=18.25 | | 4(7x-2)+5(19-3x)=3(4x+3)-6 | | 2y+110+35=180 | | 5a+7=3a-15 | | 18x+4=58 | | (6x+7)-(4+5x)=12 |